2016
DOI: 10.1155/2016/9360230
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Derivatives of Carbazole-Thiophene, Their Electronic Properties, and Computational Studies

Abstract: A series of carbazole-thiophene dimers,P1–P9, were synthesized using Suzuki-Miyaura and Ullmann coupling reactions. InP1–P9, carbazole-thiophenes were linked at the N-9 position for different core groups via biphenyl, dimethylbiphenyl, and phenyl. Electronic properties were evaluated by UV-Vis, cyclic voltammogram, and theoretical calculations. Particularly, the effects of conjugation connectivity on photophysical and electrochemical properties, as well as the correlation between carbazole-thiophene and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 57 publications
4
12
0
Order By: Relevance
“…The chemicals were used without further purification. The CdSe/CdZnSe/ZnSeS core–shell–shell quantum dots (QDs), dispersed in octane (about 15 mg mL –1 ) were provided by Najing Technology Co., Ltd. 4,4-Bis­(carbazol-9-yl)­biphenyl (CBP), 4,4-bis­((carbazol-9-yl)-3-carbaldehyde)­biphenyl ( 1 ), and 4,4′-bis­((carbazol-9-yl)-3-hydroxy­methyl)­biphenyl ( 2 ) were synthesized according to the literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The chemicals were used without further purification. The CdSe/CdZnSe/ZnSeS core–shell–shell quantum dots (QDs), dispersed in octane (about 15 mg mL –1 ) were provided by Najing Technology Co., Ltd. 4,4-Bis­(carbazol-9-yl)­biphenyl (CBP), 4,4-bis­((carbazol-9-yl)-3-carbaldehyde)­biphenyl ( 1 ), and 4,4′-bis­((carbazol-9-yl)-3-hydroxy­methyl)­biphenyl ( 2 ) were synthesized according to the literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Recent methods have been described to substitute benzo[b]thiophenes with aryl substituents, but methods to synthesize fused aryl benzo[b]thiophenes are rare [20]. Early methods were also successful to substitute carbazole with thiophene, but thienocarbazoles have not been reported so far [26]. So our approach to produce substituted benzo[b]thiophenes is completely different from earlier methods that concentrated on the benzo[b]thiophene derivatization.…”
Section: Synthesis Of the Thienocarbazolesmentioning
confidence: 97%
“…procedure and photophysical and electrochemical characterization of new extended systems based on carbazole-chromophore conjugates continue to be subject of constant research, because of their application in optical and functional materials. [14,15] Due to the intrinsic fluorescent capacity of carbazoles, several carbazole derivatives have been investigated for application as selective sensors for metal ions, anions and compounds of biological interest in homogeneous solution. [16][17][18] Recently, studies on the photophysics of several dye-carbazole couples demonstrated the relevance of these chromophoric composites for optical and sensitizing processes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%